Peran Perempuan dalam Pembangunan Desa Wonokerto, Kec. Sukorejo, Kab. Pasuruan, Jawa Timur - Handayani, Triana Dianita; Geraldy, Galang; Soleh, Mochamad Fajar; Irawan, Wika Tata; Rahmawati, Silvi (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2023)
The role of women in the development of Wonokerto village has significantly contributed to its economic recovery following the COVID-19 pandemic. The impact of their involvement is so substantial that it is often referred to as a form of superpower. This has been evident post-COVID-19, as village women successfully navigated the challenges and even managed to enhance the overall well-being of the community, including families. They capitalized on the abundance of avocado and mango farms, which yield agricultural produce every September to October. The public initiative aimed to empower women in the manufacturing and packaging sector has played a crucial role. This initiative provides insights into product packaging and effective marketing strategies, which were traditionally conducted through methods such as word of mouth or displays in glass cases in stores. Thanks to these efforts, mango avocado jam production is now attractively packaged, drawing customers' attention, and marketed online through social media platforms. The aspiration is that the production of mango avocado jam in Wonokerto village not only continues to thrive but also contributes to the overall healing and growth of the community.